Analisis Perbandingan Pendapatan Usaha Tani Kakao Sambung Samping dan Non Sambung Samping di Desa Riso Kabupaten Polewali Mandar - Rahman, Ahri; Dambe, Jumriani; Rahman, Adi Putra (Balanca : Jurnal Ekonomi dan Bisnis Islam, 2025)
This study aims to analyze the income comparison between side-grafting and local cocoa farming in Riso Village, Polewali Mandar Regency. The research method used is a quantitative approach with primary and secondary data sources, and sampling was conducted using the Slovin method. Data analysis was performed using income analysis and R/C ratio. The results show that side-grafting cocoa farming is more profitable, with a total income of IDR 72,006,107 per hectare per year. The feasibility analysis indicates that the R/C ratio for side-grafting is 19.4 and for local cocoa farming is 15.6, meaning both types of farming are feasible to run. Side-grafting cocoa farming also has the advantage of easier maintenance, which can save time and costs for farmers. However, farmers need to consider weather factors when performing grafting to increase the success of side-grafting cocoa farming. This research provides valuable information for farmers and policymakers in developing more productive and profitable cocoa farming.